PENGUKURAN KINERJA INTELEKTUAL KAPITAL PADA DOSEN TETAP DI UNIVERSITAS ESA UNGGUL JAKARTA - Septyanto, Dihin; Dewanto, I. Djoko (Lembaga Penerbitan Unversitas Esa Unggul, 2018)
AbstractUnidentified intellectual capital in universities will have an impact on low competitiveness in the MEA and Global era is a must. So the ability of Higher Education in predicting intellectual capital (IC) is the added value of the desires of intellectual capital model that will be run. This study aims to manage the value of intellectual capital to the performance of lecturers by looking at the relationship and influence in each sub variable intellectual capital. As for some variables that are processed, among others, such as: human capital, structural capital, capital relations, social capital, customer capital, which is run on Higher Education courses. Result t from each of human capital = 0.786, social capital = -0.677, relationship capital = -1.921, customer capital = 0.606 and social capital = 1.905, at t table = 1.7612. This proves that Ho is all accepted except in social capital. While the VIF value of each is human capital = 6.678, social capital = -16.014, relationship capital = 9.322, customer capital = 14.027 and social capital = 7,265, whose value is more than 0.05, this indicates that all the IC variables affect the performance lecturer.By conducting performance development at Esa Unggul University, it is deemed necessary to develop Intellectual Capital with its sub-variables in improving the performance of the University as a whole and hopefully the model can be tried to make IC Model in higher education or region. Keywords: intellectual capital, performance lecturer, tri dharma perguruan tinggi. AbstrakTidak teridentifikasikan modal intelektual di Perguruan Tinggi akan berdampak pada rendahnya kemampuan bersaing di era MEA dan Global adalah merupakan keharusan. Sehingga kemampuan Perguruan Tinggi dalam memprediksi intellectual capital (IC) merupakan nilai tambah dambaan model intellectual capital yang akan dijalankan.Penelitian ini bertujuan mengelola nilai intellectual capital terhadap Kinerja dosen dengan melihat hubungan dan pengaruh dimasing-masing sub variabel intellectual capital. Adapun beberapa variabel yang diolah antara lain, seperti : human capital, struktural capital, relasi capital, social capital, customer capital, yang dijalankan pada program studi Perguruan Tinggi. Hasil t dari masing-masing human capital = 0.786, social capital = -0.677, relationship capital = -1.921, customer capital = 0.606 dan sosial capital = 1.905, pada t tabel = 1.7612. Ini membuktikan bahwa Ho semua diterima kecuali pada social capital. Sedangkan nilai VIF dari masing-masing adalah human capital = 6.678, social capital = -16.014, relationship capital = 9.322, customer capital = 14.027 dan sosial capital = 7.265, yang nilainya lebih dari 0.05, ini mengindikasikan bahwa seluruh variabel IC memberi pengaruh terhadap kinerja dosen. Dengan melakukan pengembangan kinerja pada Universitas Esa Unggul disinyalir perlu mengembangkan Intellectual Capital dengan sub variabelnya dalam meningkatkan kinerja Universitas secara keseluruhan dan kiranya diharapkan model tersebut dapat dicoba untuk membuat Model IC pada perguruan tinggi atau wilayah yang lebih luas. Kata kunci : modal intelektual/ic, kinerja dosen, tri dharma perguruan tinggi.